Analisis Penerapan Proses Produksi Halal (PPH) Dalam Upaya Meningkatkan Kepercayaan Konsumen Pada Warung Pempek Lita Puri Masurai 11 Muaro Jambi - Neni Yuana; Rafiqi Rafiqi; Heni Pratiwi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of the Halal Production Process (HPP) and strategies that can be applied in its implementation at Warung Pempek Lita Puri Masurai II, Muaro Jambi. The research uses a descriptive qualitative approach with data collected through interviews, observation, and documentation. Data were analyzed using the SWOT analysis method. The results show that Warung Pempek Lita has applied halal principles in every stage of production, including raw material selection, processing, packaging, and distribution. Furthermore, the SWOT analysis identified four strategies to strengthen the implementation of HPP in order to increase consumer trust: (1) SO Strategy (Strength-Opportunities): strengthening product image by highlighting the use of fresh ingredients without preservatives and maintaining a clean, independent production process; (2) WO Strategy (Weakness-Opportunities): applying for training and mentoring from halal institutions such as MUI or LPPOM to enhance the owner’s knowledge of halal standards and the Halal Assurance System (SJPH); (3) ST Strategy (Strength-Threats): educating consumers that pempek is produced independently and carefully in accordance with halal principles to foster customer loyalty despite tight competition; (4) WT Strategy (Weakness-Threats): separating the production kitchen from the household kitchen, even in a simple form, as a commitment to halal principles and improved production hygiene..